Theoretical Investigation of Six-Mode Multi/Demultiplexer Based on Fused-Type Multicore Fiber Coupler - Shoko Nishimoto; Takeshi Fujisawa; Yusuke Sasaki; Hitoshi Uemura; Kunimasa Saitoh (IEEE Photonics Journal, 2016)
A six-mode $(\text{LP}_{01}/\text{LP}_{11{ab}}/\text{LP}_{21{ab}}/\text{LP}_{02})$ multi/demultiplexer based on a fused-type multicore fiber coupler is proposed, and the coupling characteristics are investigated. The multi/demultiplex operation is achieved by a phase matching between the desired mode of center core and the $\text{LP}_{01}$ mode of the outer core in the elongated region of the fused-type multicore fiber coupler. From the numerical results based on the beam propagation method, it is found that the coupling efficiencies between the $\text{LP}_{01}$ and $\text{LP}_{11}/\text{LP}_{21}/\text{LP}_{02}$ modes are more than −0.1 dB, and the crosstalk is lower than −20 dB at the wavelength of 1550 nm.